КЛИНИКО-ЭКОНОМИЧЕСКАЯ ЭФФЕКТИВНОСТЬ СКРИНИНГА ВРОЖДЕННОГО ГИПОТИРЕОЗА - Абазова, Залина Хасановна; Борукаева, Ирина Хасанбиевна; Шибзухова, Лаура Анзоровна; Шибзухов, Тимур Анзорович; Водахова, Валентина Аркадьевна (FORCIPE, 2022)